The numerical simulation of droplet impact on surfaces is conducted using the SPH-DEM method - Shilong Bu; Daming Li; Hu Tao; Wenjie Hou (PLoS ONE, 2025)
The process of liquid droplet impinging upon the surface of particles entails complex dynamics and significant deformation. In this study, the smoothed particle hydrodynamics (SPH) method coupled with the discrete element method (DEM) is employed to investigate the motion process of liquid droplet impacting the particle surface. A surface tension model is introduced into the SPH motion equation to calculate the motion of the liquid droplet. In the SPH-DEM coupling module, the viscous force and capillary force between the liquid droplet and the particles are taken into account. The surface tension model is verified through two cases: the free deformation process of a stationary square liquid droplet and the impact of a liquid droplet on a hydrophobic wall. The accuracy of the DEM model is validated through experimental verification of dry particle collapse. And the experimental results validate the accuracy of the SPH-DEM model in simulating the liquid droplet impact on the particle surface. The simulation results are in good agreement with the experimental ones. Utilizing the SPH-DEM model, the influences of the droplet impact velocity and the particle diameter on the rebound phenomenon after the water droplet impacts the particle wall of the powder bed are respectively investigated. The results indicate that the higher the droplet impact velocity and the smaller the diameter of the powder bed particles, the faster the rebound rate of the droplet after impacting the powder bed layer.